Metal-Organic Frameworks-Based Electrocatalytic Reduction of CO2 - Zhang, Chao (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Given the increasing emphasis on carbon dioxide (CO2), diverse approaches have been developed and then used to address the issue. Metal-organic frameworks (MOFs) have shown promise in catalyzing the electrochemical reduction of CO2. Different types of MOFs have investigated, including Cu-MOFs, Ce-MOFs, and hybrid composites, in order to enhance the catalytic selectivity, activity, and stability of electrocatalysts. MOFs possess distinct structural characteristics such as a large surface area, adjustable pore architectures, and numerous active sites, which provide effective adsorption, activation, and subsequent electrochemical reduction of CO2. The inclusion of metal centres, such as copper, silver, and cobalt, in MOFs has shown a strong preference for valuable chemical products, such as ethylene, formate, methane, and acetic acid. Incorporating MOFs with carbon-based electrodes or photosensitizers has significantly improved the catalytic efficiency and the speed at which charge is transferred in CO2 electroreduction processes. Nevertheless, there are still obstacles to overcome, such as the need to optimize the composition of catalysts, manage particle size, and provide scalability for use in industrial applications. Further study is necessary to expand the range of electrochemical techniques and reaction conditions, enhance the longevity of catalysts, and explore the potential of utilizing these types of catalysts for the specific conversion of CO2 into other valuable liquid fuels.